TANGGUNG JAWAB JABATAN DAN TANGGUNG JAWAB PRIBADI DALAM PENGGUNAAN DISKRESI SEBAGAI INSTRUMEN PELAYANAN PUBLIK (PUBLIC SERVICE) - Adam Setiawan; Nehru Asyikin (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2020)
AbstractDiscretion is part of the authority to act freely by government officials to ensure the implementation of public services. The instrument of discretion is attached to the functionary and used to overcome problems where there is no law. But sometimes the use of discretion causes harm to the community, so it is important to know the form of official responsibility whether it is functionary responsibility or personal responsibility. Government officials who use discretion, as long as the action is carried out within the formal environment of their authority or carried out in the context of exercising office authority, all consequences that arise will be the responsibility of the functionary. While personal responsibility is related to maladministration in the use of authority and public service.IntisariDiskresi merupakan bagian dari kewenangan bertindak bebas oleh pejabat pemerintah untuk menjamin terlaksananya pelayanan publik. Instrumen diskresi melekat pada jabatan dan dipergunakan untuk mengatasi persoalan yang tidak ada hukumnya. Namun terkadang penggunaan diskresi menyebabkan kerugian bagi masyarakat sehingga penting mengetahui bentuk tanggung jawab pejabat apakah itu tanggung jawab jabatan atau tanggung jawab pribadi. Pejabat pemerintah yang menggunakan diskresi, selama tindakan itu dilakukan dalam lingkungan formil wewenangnya atau dilakukan dalam rangka melaksanakan kewenangan jabatan, semua konsekuensi yang timbul akan jadi tanggung jawab jabatan. Sedangkan tanggung jawab pribadi berkaitan dengan maladministrasi dalam penggunaan wewenang maupun public service.